(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
White corn cultivar (ezraa 7) was used to study an effect of irrigation dates, potassium fertilization, and zinc spraying and the interaction between them on some morphological, physiological and productivity indicators of white corn plants. And by designing the sectors split plots for two and three replications, as the irrigation dates were distributed to the main plots (7,14,21 days) in addition to the control treatment (14 days), while the secondary plots included potassium fertilization rates (60,80,100 kg / ha), And spraying with zinc (0.4,0.8,1.2 kg / ha). In the village of Salhab in the Al-Ghab region - of Hama Governorate, in the 2020 agricultural season. The interaction between the 7-day irrigation time with potassium 60 kg / ha and zinc concentration was 0.4 kg / ha, with characteristics of plant height (181.67 cm) and stem diameter (19.37 mm). The overlap between irrigation time of 14 days with potassium concentration of 60 kg / ha and zinc at 1.2 kg / ha outperformed the characteristics of branching (3.7 branches) and grain yield (1.62 tons / ha). The overlap between the irrigation time for 7 days with the concentration of potassium 80 kg / ha and zinc was 0.8 kg / ha on the bank of the number of leaves (12 leaves). The overlap between the irrigation time was 7 days with the concentration of potassium 80 kg / ha and zinc at 0.4 kg / ha as the length of the last salamia (43.83) cm The overlap between the irrigation time for 7 days with the concentration of potassium 60 kg / ha and zinc was 0.8 kg / ha as the leaf flat (368.87 cm2) and the overlap between the irrigation date was greater than 14 days with the concentration of potassium 60 kg / ha and zinc 0.4 kg / ha as a weight of 100 grains) 3.36g)